The fixed-cost dilemma: what counts when counting cost-reduction efforts? - Rauh, Stephen S; Wadsworth, Eric; Weeks, Bill (Journal of the Healthcare Financial Management Association, 2010)
The high fixed-cost structure of hospitals and the predominance of "joint costs" mean few truly variable costs can be captured by small or incremental cost reduction strategies. Many of the proxy metrics used to measure cost savings, such as length of stay and readmissions, typically does not reflect true cost savings, but should be seen as measures of additional capacity with the potential for added revenue. To achieve true savings, hospitals should consider reducing capacity when possible and making better use of the remaining capacity, increasing throughput, and reducing costs per discharge.